Sedimentary facies and engineering geological characteristics of Holocene deposits in the coastal area of Tien Lang district, Hai Phong city - Loi, Vu Van (Vietnam Journal of Earth Sciences, 2016)
Infrastructural construction has recently been an important issue in the coastal zone of Tien Lang district, Hai Phong city. The area is characterized by soft layers of the Holocene deposits, that leads to difficulties in engineering construction and land use planning of the area. Geological investigation has defined 8 facies and subfacies of Holocene deposits in the coast of Tien Lang district with their typical sedimentary and engineering geological characteristics. In the view point of engineering geology, these deposits are almost soft soil layers. Their significant thicknesses and wide area of distribution, require specific consideration in construction design and ground reinforcement to ensure the longterm stability of engineering structures. References Nguyễn Tuấn Anh (chủ biên), 2006: Dự án sản xuất thử nghiệm “Xây dựng hệ thống các điểm Trắc địa sử dụng công nghệ GPS độ chính xác cao trong việc quan trắc biến dạng lớp vỏ Trái đất và cảnh báo thiên tai ở khu vực Việt Nam”. Lưu trữ tại Viện Khoa học đo đạc và bản đồ, Hà Nội. Vy Quốc Hải, 2009: Xác định chuyển dịch tuyệt đối khu vực lưới GPS Tam Đảo - Ba Vì, Tạp chí Địa chất số 311, 3-4, tr.22-30. Vy Quốc Hải, Trần Đình Tô và Ngô Văn Liêm, 2011: Xác định chuyển dịch hiện đại đới đứt gãy Sông Hồng theo số liệu lưới GPS Tam Đảo - Ba Vì (1994-2007). Tạp chí Các Khoa học về Trái Đất, tr.474-479. Ngô Văn Liêm , 2011: Đặc điểm phát triển địa hình trong mối liên quan với địa động lực hiện đại đới đứt gãy Sông Hồng. Luận án Tiến sỹ Địa lý, Hà Nội. Lưu trữ Thư viện Viện Địa chất, Hà Nội. Nguyễn Đăng Túc, 2002: Một số đặc điểm tân kiến tạo hệ đứt gãy Sông Hồng-Sông Chảy. Luận án Tiến sĩ, Hà Nội. Lưu trữ Thư viện Quốc gia, Hà Nội. Rolf Dach, Urs Hugentober and Peter Walser, 2008: Bernese GPS Software Version 5.0. Astronomical Institute, University of Bern.